State Judgement Model of the Coal and Rock Medium and Its Engineering Application - Chuanqi Zhu; Lei Wang; Xiangang Han (Advances in Civil Engineering)
In the loading and failure process of the coal and rock medium, with the increasing of the damaging and failure extent, the medium state gradually changed from the continuous, the quasicontinuous, and the discontinuous to the loose successively. To evaluate the damaging failure extent of the coal and rock mass and distinguish the state of the coal and rock mass medium, first, the medium state index was defined based on the acoustic wave propagation model. Then, based on the coal mass in the working face 8512 in the Chenjiagou Coal Mine in China, the acoustic character and the mechanical character experiments were conducted. Through experiments, the variation law of the ultrasonic wave velocity and the medium state index of the coal mass with the strain under the compressive state were acquired; with the increasing of the strain, the medium state indexes successively experienced the variation process including stabilising around 0, slow increasing, dramatic increasing, and stabilising around 1. Then, based on the variation law of the medium state index, the coal and rock mass medium state judgement model was constructed. This model was applied to judge the coal mass medium state. After it, the mudstones in the roof of the same working face were regarded as the research object, the mudstone medium state was divided into 4 types according to the medium state judgement model, namely, continuous, quasicontinuous, discontinuous, and bulk solid, and the mudstone failure state was basically consistent with the continuous, quasicontinuous, discontinuous, and bulk solid state. The adaptability and rationality of the judgement model was verified. Finally, engineering application of the judgement model was conducted. The distribution law of the top coal with different medium state was acquired. In the top coal that was 186 m away from the working face, it belonged to the continuous medium state. As for the top coal that was 6 m to 186 m far away from the working face, it was under the quasicontinuous medium state. For the top coal that was 3 m to 6 m far away from the working face, it was under the discontinuous medium state. For the top coal that was less than 3 m far away from the working face and behind the working face, it belonged to the bulk solid medium state. The state judgement model can successfully distinguish the medium state of the coal seam and mudstones in the roof in the working face 8512. This provided a new approach to evaluate the damaging failure extent of the coal and rock medium in the Chenjiagou Coal Mine.